Multi-Sector Collaboration for Capacity Building in Developing Countries: A Context for Theorizing Transformative Learning at a Systems Level - Lucas Hill; John Bonnell; John Drikx; Tom Smith (Adult Education Research Conference, 2014)
Multi-sector collaboration (MSC) offers a means to transform agricultural education and training (AET) capacity in developing countries. Drawing upon transformative learning theory and adult education concepts, this paper describes a theoretical lens to understand and advance adult learning through MSC to produce a more coordinated and sustainable workforce.